Development of Green/Skin-friendly Textiles by Minimizing Formaldehyde Content in Pigment Printing - Siyal, Muhammad Irfan; Saleemi, Sidra; Soomro, Noorullah; Qureshi, Raja Fahad (Journal of Design and Textiles, 2024)
This study aims to reduce the content of formaldehyde in pigment printed cotton fabric with deep shades. A hand screen printing method was applied using various curing temperatures and concentrations of urea for preparation of skin-friendly products. The woven, bleached fabrics were printed following a precise process of screen printing and these samples were dried and curried for proper fixation. Standard test procedures were followed to assess the content of H-CHO (formaldehyde) during washing and rubbing. H-CHO contents were instantly reduced by increasing the temperature of the printed fabric during curing. The best outcome for wet and dry fastness of rubbing was achieved at 160˚C, while a little enhanced rubbing outcomes were observed when the concentration of urea was 2% at a fixation temperature of 150˚C. The final product may be effectively used for clothing purpose, meeting the OEKO-TEX® Standard 100 standard for low formaldehyde content.